EFEK LATIHAN SKIPING DAN JOGING TERHADAP CARDIORESPIRATORY FITNESS PADA SISWA SMPN 208 JAKARTA - Nur Achirda; Alisa Qtrunnada; Mohammad Ali (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2022)
Background: Adolescence is the transition period of an individual from childhood to adulthood.Cardiorespiratory Fitness can play a role in school achievement. Cardiorespiratory Fitness is the ability of the cardiovascular and respiratory systems to perform a physical activity. To improve it can be done with skipping and jogging exercise. Objective: To determine the effectiveness of skipping and jogging exercises on Cardiorespiratoy Fitness in students of SMPN 208 Jakarta. Research Methods : This study is a quasi-experimental with Two Group Pre and Post Test approaches. The sample was obtained by purposive sampling method with the number of each group as many as 17 people in the skipping group and jogging group. Result : Statistical test using the SPSS program in the Paired sample t-test, the average value in skipping group was 10.98 and the jogging group was 9.28. test results Independent sample t-test obtained p value of 0.74, where p>0.05. Conclusion: Both exercises have the same effect in increasing Cardiorespiratory Fitness in students.